Analisis Pengaruh Investasi Energi Bersih dan Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi Berkelanjutan di Negara-Negara ASEAN Periode 2014-2023 dalam Perspektif Ekonomi Islam - Khasanah, Uswatun; Pratomo, Dimas; Supriyaningsih, Okta (Universitas Islam Lamongan, 2025)
With increasing attention to environmental and sustainability issues, investment in clean energy is crucial to drive economic growth that is not only efficient but also sustainable. In addition, human development index (HDI) as an indicator of people's quality of life also plays an important role in influencing economic growth. This study aims to analyze the effect of clean energy investment and human development index on sustainable economic growth in ASEAN countries from the perspective of Islamic economics in the period 2014-2023. The analysis method used is VAR and VECM analysis. The results showed that sustainable economic growth and clean energy investment did not have a causal relationship but in the long-term VECM regression clean energy investment had a positive and significant effect on economic growth. While the human development index variable has a mutual effect with sustainable economic growth. The results of the causality test also show that clean energy investment has no causal relationship with the human development index.